Concept of mind in Indian philosophy, Western philosophy, and psychology - Durga Tanisandra Krishnappa; Melukote Krishnamurthy Sridhar; H R Nagendra (Wolters Kluwer Medknow Publications, 2020)
This article makes an explorative journey into the concepts of mind as explained in the Indian philosophical traditions and Western psychology. The article explains about knowledge domains in the traditions and their distinctive features, different connotations and denotations of mind, and the different methods being used in explaining mind. Yet, they may not appear to be opposed or conflicting in nature. The article elaborates on the concepts such as mind (manas) and mind apparatus (citta) in Indian philosophical traditions and compares with the traditional Western psychology where the primary emphasis is given to the mind. The article indicates that in the Indian philosophical tradition, mind helps in knowing consciousness, whereas in the Western paradigm, mind becomes the subject as well as the object of knowing. Knowing gives an understanding of the truth and could lead to realization. In the Eastern tradition, knowing becomes a being and becoming. This knowledge of the self (ātman) helps the individual in attaining happiness (sukha) and welfare (abhyudaya) in this world and realization of the supreme reality (Brahman) leading to liberation (mokṣa). Thus, knowing and understanding about consciousness become complementary in both the traditions.